“Microdureza superficial entre dos tipos de resinas nanoparticuladas y el momento de pulido. Estudio in vitro”. - Rodriguez Asmat, Roxana Madaleyni (2020)
This research work aimed to determine what is the difference in the surface microhardness of discs with the resin "A" (Tetric N Ceram Bulk Fill®) and a composite resin "B" (Tetric N Ceram®), subjected to different moments polishing. 78 resin discs of 6 mm diameter and 4 mm height were obtained, divided into 6 groups. Monoincremental and double increment techniques wer used for resin A and B respectively. On each one, a celluloid tape and slide sheet, digital pressure was exerted and light-cured (intensity ≥ 1000 mW / cm2). For finishing and polishing, 320 grit water sandpaper and the Diacomp Plus Twist® system were used. he groups with polishing at 10 minutes and at 24 hours were stored in distilled water at 37 ° C in an oven, inally the microhardness tests were carried out with an INDETEC ® (load of 5 Kg-F for 10 sec.). The btained data were processed in SPSS-25, in the statistical analysis the F test of the analysis of variance. The values obtained for finishing and immediate polishing, at 10 minutes and 24 hours for each resin re: For resin "A" (59.76, 63.21, 64.09 HV respectively), for "B" (54.52, 69.58, 72.55 HV respectively). In conclusion, the surface microhardness in composite resin discs (Tetric N Ceram® resin), with polishing at 24 hours in vitro showed the highest values compared to immediate polishing of Tetric N-Ceram® and Tetric N Ceram Bulk Fill®. The surface microhardness decreases when polishing is immediate in any of the resins.